Analysis of Financial Performance with the Camel Method (Case Study of Banking Companies Listed on the Indonesia Stock Exchange for the 2016-2018 Period) - Solihin, Agung; Fathihani, Fathihani (Dinasti Publisher, 2024)
This study aims to analyze the Implementation of Financial Ratios to Assess the Financial Performance of Banking Companies Listed on the IDX. The approach in this study is to use a quantitative approach, and based on its objectives, this type of research is causal, namely research that explains the effect of an independent variable on the dependent variable. Independent variables in this study include Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Net Interest Margin (NIM), Operating Expenses on Operating Income (BOPO), Finance to Deposit Ratio (FDR) and for the dependent variable in this study is Financial Performance projected by Return On Asset (ROA). The population of this study are banking companies listed on the Indonesia Stock Exchange which amounted to 44. The sample determination procedure uses a non-probability sampling method in the form of purposive sampling, which is a sampling technique with certain considerations. The considerations taken are banks that are included in the 6 banks with the largest profit achievements in 2018.